KARMA DAN ETOS KERJA DALAM AJARAN BUDHA - Rusli, Ayu Rustriana (Al-Adyan: Journal of Religious Studies, 2020)
This article aims to describe the relation between karma and work ethic in Buddhism which centred to the understanding of karma. There are two understanding of karma, namely: First, karma means the fatalism; Second, karma means optimism. The second meaning related to the work ethic based on Budhisme.  One of the concept of karma which most related to the work ethic is Karma Vipaka. It motivates Buddhists always be optimistic, earnest, diligent, tenacious, work hard, be honest, and be responsible for all actions. Based on this concept born the concept of work ethic that emphasizes that nothing will determine the fate of humans except humans themselves.Tulisan ini bertujuan untuk menggambarkan hubungan antara karma dan etos kerja dalam agama Budha yang berpusat pada konsep karma. Ada dua pemahaman tentang karma, yakni: pertama, karma bermakna fatalisme; kedua, karma bermakna optimisme. Makna kedua terkait dengan etos kerja dalam agama Budha. Salah satu konsep karma yang sangat terkait dengan etos kerja adalah Karma Vipaka. Karma ini memotivasi umat Budha untuk selalu optimis, sungguh-sungguh, rajin, ulet, bekerja keras, jujur, dan bertanggung jawab atas semua tindakan. Berdasarkan hal ini lahirlah konsep etos kerja yang menekan bahwa tidak ada yang akan menentukan nasib manusia kecuali manusia itu sendiri.